PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN DOSEN PELAKSANA KERJA SAMA PADA BIRO KEMITRAAN ITB MENGGUNAKAN METODE DATA MINING - Muhammad Alfarisi, Zidane
Bandung Institute of Technology (ITB) always strives to improve partnerships to expand the partnership network at ITB. To realize this goal, there is one of ITB's work units, namely the Partnership and Strategic Management Section under the ITB Partnership Bureau. One of the problems faced in this section is related to achieving the target number of collaborations. On the other hand, ITB has many lecturers who have the potential to be implementers of collaborations. The problem occurs because there is no more structured processing to be able to produce information about the expertise of ITB lecturers. At this time, the determination of implementing collaboration lecturers is carried out inefficiently because it is still done manually and sporadically.